2014
DOI: 10.1002/anie.201404742
|View full text |Cite
|
Sign up to set email alerts
|

7‐Aryl‐7‐deazaadenine 2′‐Deoxyribonucleoside Triphosphates (dNTPs): Better Substrates for DNA Polymerases than dATP in Competitive Incorporations

Abstract: A series of 7-substituted 7-deazaadenine and 5-substituted cytosine 2'-deoxyribonucleoside triphosphates (dNTPs) were tested for their competitive incorporations (in the presence of dATP and dCTP) into DNA by several DNA polymerases by using analysis based on cleavage by restriction endonucleases. 7-Aryl-7-deazaadenine dNTPs were more efficient substrates than dATP because of their higher affinity for the active site of the enzyme, as proved by kinetic measurements and calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 47 publications
7
40
0
3
Order By: Relevance
“…The 7‐position was chosen for linkage because it is known to be polymerase‐compatible, avoiding destabilization of the helical structure of DNA . Furthermore, it is reported than 7‐substituted 7‐deaza‐dATPs can even be better substrates for polymerases than dATP . In this direction, the introduction of an acetylene linker between the nucleobase and the POM label was expected to facilitate incorporation of the modified nucleotides during polymerase‐mediated elongation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The 7‐position was chosen for linkage because it is known to be polymerase‐compatible, avoiding destabilization of the helical structure of DNA . Furthermore, it is reported than 7‐substituted 7‐deaza‐dATPs can even be better substrates for polymerases than dATP . In this direction, the introduction of an acetylene linker between the nucleobase and the POM label was expected to facilitate incorporation of the modified nucleotides during polymerase‐mediated elongation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We decided to synthesize 2'-deoxycytidine and 2'-deoxy-7-deazaadenosine derivatives as one example of a pyrimidine and one example of purine analogue (please note that 7-substituted 7-deazapurine dNTPs are generally used instead of purine derivatives due to their excellent substrate activity with DNA polymerases). [19][20][21]26 5 Scheme 1. Synthesis of Bodipy-linked dNTPs.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the Hocek lab, who has spent considerable effort studying and applying base modified dCTP and dATP in vitro, has observed that various family A and family B polymerases preferentially incorporate 7-aryl-7-deazaadenine 2′-deoxyribonucleoside triphosphates over unmodified dATP. 34 Modified nucleic acid enzymes have been pushed the boundaries of catalytic potential for nucleic acid polymers. One particularly challenging catalytic reaction is amide hydrolysis.…”
Section: Copolymerization Of Nucleobase Modified Nucleosidementioning
confidence: 99%